Perbedaan pola makan pasien diabetes melitus (DM) dan non-DM di Pusat Layanan Kesehatan Masyarakat Kota Surakarta - Siti Zulaekah; Imelda Anggraini; Yumailita Setiawati; Yuli Kusumawati (UHAMKA PRESS, 2022)
An unhealthy diet is one of the risk factors for non-communicable diseases (PTM), especially diabetes mellitus (DM) and hypertension. The application of a healthy lifestyle is the management of DM with the application of medical nutrition therapy. This study aimed to analyze the differences in energy intake, carbohydrates, cholesterol, glycemic load of food consumed between DM and non-DM patients at Chronic Disease Management Program (CDMP) in the Surakarta Primary Health Center (PHC). This observational study was conducted with a case control design. The samples were 32 DM patients and 32 non-DM patients participating in CDMP at the Jayengan, Penumping, Sibela, Pucang Sawit, Gajahan, and Manahan PHC. The samples were taken by consecutive sampling. Dietary data including energy intake, carbohydrates, cholesterol and glycemic load consumed by subjects during the last three months were obtained through direct interviews using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) form and analyzed using the Nutri Survey 2007 program. Analysis of differences in energy intake, carbohydrates and cholesterol in both groups using the Independent T-Test. The results showed that the diet pattern in the DM group has the sufficient energy intake (40.6%), most of the carbohydrate intake in the DM group was excessive (87.5%). Cholesterol intake in the DM group was as recommended (50%), in the DM group, the consumption of the glycemic load was high (97.3%). There were differences in energy intake and glycemic load between DM and non-DM patients at the Surakarta City Health Center. On the other hand, there were no differences in carbohydrate and cholesterol intake between DM and non-DM CDMP patients.